Ecclesiastical law and ethnic minorities with particular reference to Hungarian minorities in East-Central Europe - Kerekes, Laszlo (University of Ottawa (Canada), 2003)
The Church as the new People of God from its foundation is Catholic and universal. The Church in its mission has greatly appreciated the different cultures and had consistently emphasized the value of national belonging. Different languages and cultures were always a challenge, signs of the times, when the Church carried out its salvific mission. This values were incorporated (although not explicitly) into the legislation of the Church in the light of its catholicity. East-Central Europe is the gathering place of many nations who lived together for centuries. Political systems often created tensions among various nationalities and religions, because in East-Central Europe religion and national identity often overlap. With the dismemberment of Hungary in 1918, the tension in the so-called successor states between the Hungarian minority and the new ruling majority influenced the life of particular churches and Catholic communities. During the Communist regime, the problem of national minorities was for all practical purposes overlooked. The political philosophy based on the "dictatorship of the proletariat" left little place for various cultures, and, under the red flag of Communism, the political ideas of the majority prevailed. After the collapse of the communist regime in 1989, national minorities had the freedom to give voice to their desire for the recognition of their fundamental human rights. The various nationalities in East-Central Europe, including national minorities, are not immigrants. They became minorities because of historical and political situations. With the changes of civil borders they were removed from the body of the mother state. Their home and cultural roots are at hand, but they find themselves in an alien culture. The Church created various means and structures for the pastoral care of immigrants in view of their exceptional situation. However, this cannot be fully applied in the situation of ethnic minorities, because certain factors make their situation different. One of these is the divided particular Churches and hierarchy, which were divided also by civil borders. In the newly created and rearranged particular Churches, the minority was often surrounded by a "hostile" majority and not by a welcoming country as in the case of immigrants. Another factor which characterizes the situation of ethnic minorities is that any attempt to establish ecclesiastical structures based on nationality (personal diocese, personal parish), might be interpreted by the majority as a breeding ground for nationalism, and could even incite their fear of a possible change of civil borders, placing the integrity of the state in jeopardy. Pope John Paul II, in his World Day of Peace Message in 1989, summarized those values, which ecclesiastical legislation has to rely on namely, the right of an ethnic minority to its language, culture and education, as well as the duty of ethnic minorities toward the majority culture. The A. presents some practical possibilities and perspectives in creating a culture of peace and some relatively simple possibilities for ecclesiastical legislation related to ethnic minorities.
Keywords: Religion, General.; Law.; Sociology, Ethnic and Racial Studies.